Levels of physical activity and physical fitness in young people and adolescents with respect to sex and hours of physical education (Revista Chilena de Rehabilitación y Actividad Física, 2023)
Among the causes of the prevalence of obesity and overweight in the population is the lack of physical activity. According to WHO data, more than 80% of adolescents in the world have an insufficient level of physical activity. Objective: To analyze and compare the levels of physical activity, physical condition and BMI of eighth grade and first middle school students of a school in the city of Talca. Methods: We evaluated 136 students with an average age of 13.6 years old. Sociodemographic data were established, physical activity and physical condition levels were evaluated by means of evaluations and self-report tests. Results: No significant differences were found in BMI between males and females (22.3±2.7 vs. 21.2±4.8, p=0.17). There was a low mean of 4.48±1.1 of physical activity, women presented a lower score (4.14±1.09) compared to men (4.85±1.05) (p
Keywords: student; physical education; health; obesity; school